Pendidikan Kewanitaan dalam Surat an-Nuur ayat 31 Tafsir al-Azhar - Sri Rahmah Mubarokah; Syamsul Bakri (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2022)
Allah SWT has given the command to His servants, especially women, to always lower their eyes and to cover their aurat. Even a few of them do not know what aurat, mahram, permittable self-preening and to whom their precious jewelry may be shown. This is important to commit Allah’s commands as stated in His commandment on Qur’an Surah an-Nuur verse 31. This research aims to describe women’s education values in Qur’an Surah an-Nuur verse 31 on tafsir al-Azhar by Buya Hamka. This research is included in library research. The information obtained as a whole was taken from various libraries such as journal articles and other related information sources of reports. This research used primary data as the main source and secondary data as supporting data. The results of this research show that education values in Qur’an Surah an-Nuur verse 31 and its application on Islamic education are: Muslim women should always keep their eyes, keep purity (‘iffah), and cover their aurat.